Concerning the Existence of a Discrete Space - Ahmed Isam (Jordan Journal of Physics, 2025)
Loop quantum gravity is considered to be one of the two major candidates for a theory of quantum gravity. The most appealing aspect about this theory is that it predicts that space is not infinitely divisible, but that it has a granular structure. This paper illustrates a missed proof which validates the previous prediction of the theory. It does not prove or validate the model of quantized geometry of the spacetime which is predicted by the theory itself, but instead, it proves the necessity of space discreteness, and the existence of space quanta due to a simplefact or observation which isthe existence of the origin position in a coordinates system. This is done in this paper by defining one of the major concepts in physics, which is the quantization concept, in a simple way, and applied directly to the observation. Although the area of quantum gravity – in general – requires a sophisticated level of mathematics, this paper was built on a simple mathematical level to make it accessible to any reader. Keywords: Quantum gravity; Quantization concept; Discrete space.